The origins of a novel butterfly wing patterning gene from within a family of conserved cell cycle regulators (2015)
A major challenge in evolutionary biology is to understand the origins of novel structures. The wing patterns of butterflies and moths are derived phenotypes unique to the Lepidoptera. Here we identify a gene that we name poikilomousa (poik), which regulates colour pattern switches in the mimetic Heliconius butterflies. Strong associations between phenotypic variation and DNA sequence variation are seen in three different Heliconius species, in addition to associations between gene expression and colour pattern. Colour pattern variants are also associated with differences in splicing of poik transcripts. poik is a member of the conserved fizzy family of cell cycle regulators. It belongs to a faster evolving subfamily, the closest functionally characterised orthologue being the cortex gene in Drosophila, a female germ-line specific protein involved in meiosis. poik appears to have adopted a novel function in the Lepidoptera and become a major target for natural selection acting on colour and pattern variation in this group.